Complications of laparoscopic cholecystectomy - Barreiro, Claudia; Delbene, Roberto; Moure, Luis; Praderi Gambardella, Luis A; Tchekmedyian, Vartan; Matteucci, Pablo; Estapé, Gonzalo (Cirugía del Uruguay, 2000)
Laparoscopic cholecystectomy has become the procedure of choice in liver approach. Howeve, its development and widespread use appear to be associated with a higher incidence of injuries, particular/y in the common bife duct.